Sinergisme Pupuk Hayati Konsorsium sebagai Penggerak Pertumbuhan Vegetatif dan Produksi Sulur pada Stroberi (Fragaria × ananassa Duch.): A Systematic Review - Ranindia Fahma Kumala (Jurnal Solum, 2026)
Soil degradation driven by intensive chemical fertilization poses a major challenge to modern strawberry (Fragaria × ananassa Duch.) cultivation, particularly in securing high quality vegetative growth and adequate runner supply for propagation. This review examined the synergistic roles of consortium biofertilizers in addressing both dimensions through a Systematic Literature Review (SLR) guided by the PRISMA framework. Searches across five scientific databases ScienceDirect, Scopus, Web of Science, SpringerLink, and Google Scholar, retrieved 1,996 articles; following rigorous screening, 25 articles published between 2016 and 2026 were retained for final synthesis. The findings demonstrate that PGPR consortia increased plant height by up to 51.9%, leaf number by 97.5%, leaf area by 40.5%, and root fresh weight by 68.6% relative to controls. Runner production improved substantially, ranging from 35.66% to 210.85%, with the highest output reaching 32.7 runners per plant. These gains are mediated through three interconnected pathways: (1) enhanced N, P, and K availability via biological nitrogen fixation and phosphate solubilization; (2) phytohormone production (IAA, gibberellins, and cytokinins) that activates axillary meristems toward runner differentiation; and (3) expanded nutrient absorption facilitated by arbuscular mycorrhizal hyphal networks. Consortium biofertilizers consistently outperform single-microbe inoculants and hold strong promise as an eco-friendly strategy for productive and sustainable strawberry propagation systems. Key words : microbial synergism, PGPR, arbuscular mycorrhizal fungi, phytohormone, axillary meristem, rhizosphere